Occupational opportunities in the GDR : a privilege of the older generations? - Huinink, Johannes [Verfasser]; Solga, Heike [Verfasser] (My University, 1994)
"Compared to the amount of information available concerning the other former state socialist countries there is a research deficit regarding the rates and patterns of occupational mobility in the GDR. This deficit is especially unfortunate since the GDR can be characterized as having been a state socialist country par exellence where many crucial features of state socialism were realized in a more consequential way than, for example, in Poland or Hungary. In this article the authors try to give a more thorough analysis of occupational opportunities and their historical change in the GDR. The analysis is based on work histories of 1141 East German men born in four cohorts: 1929-31, 1939-41, 1951-53 and 1959-61. These retrospective data are taken from the East German Life History Study of the Max Planck Insitut for Human Development and Education, Berlin. Based on descriptive analysis and logit regression models the main conclusion is that starting at a high level in the post- war-period, occupational opportunities of men decreased over cohorts, but by the 1980s they were not completely eliminated by any means. Overt system loyalty, i.e., party membership or having an official function organization, improved the changes of upward mobility in all cohorts." (author's abstract, IAB-Doku) ((en)) In der Studie wird versucht, die beruflichen Entwicklungsmöglichkeiten im Zeitablauf in der DDR zu analysieren. Die Analyse basiert auf Berufsbiographien 1141 ostdeutschen Männern der Alterskohorten 1929-31, 1939-41, 1951-53 und 1959-61. Der wichtigste Befund der deskriptiven Analyse und der Logit- Regressionsmodelle lässt sich dahingehend zusammenfassen, dass der in der Nachkriegszeit anfänglich hohe Level beruflicher Entwicklungsmöglichkeiten über die Alterskohorten allmählich abnahm, aber in den achtziger Jahren noch nicht völlig verschwunden war. Systemloyalität verbesserte die Chance zum beruflichen Aufstieg in allen Kohorten. (IAB2)
Keywords: G 1.3.3.3 Mobilität; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.1 Bildungs- und Berufswege; G 2.4.4 Biografiegestaltung; Berufliche Mobilität; Beruflicher Status; Intergenerationenmobilität; Quantitative Angaben